QUERCETIN EFFECTIVENESS IN THE COMPLEX HYPOLIPIDEMIC THERAPY OF PATIENTS WITH NONALCOHOLIC FATTY LIVER DISEASE WITH METABOLIC SYNDROME - Kravchenko, L.S.; Appelhans, O.L.; Poliakov, A.E.; Borysiuk, I.Yu.; Ivanova, Y.I.; Neskoromna, N.V.; Rosumenko, M.V. (World of Medicine and Biology, 2022)
86 patients with metabolic syndrome and comorbid nonalcoholic fatty liver disease were carried out general clinical and laboratory-instrumental examinations. After registration of the initial data, the patients were divided into 2 groups: 41 patients with the use of rosuvastatin were added quercetin 40 mg 3 times a day for 3 months to the basic therapy (group 1). The basic therapy with rosuvastatin only was carried out in 45 patients (group 2). After the treatment on the 90th day, positive changes in lipid metabolism were registered in all the patients. The group 2 patients had a decrease in the level of low-density lipoproteins by 21.2 % (р˂0.05), an increase in high-density lipoproteins by 43.3 % (р˂0.05). The liver transaminase activity was lower by 15.0 %, concentration of pro-inflammatory interleukin-6 and cytokeratin-18 – by 10.0 % (р˃0.05). In patients of the group 1 the level of low-density lipoproteins decreased by 39.5 % (р˂0.05), the triglycerides – twice, activity of transaminase – by 30.0 % (р˂0.05). The high-density lipoproteins level increased by 72.0 % (р˂0.05). Interleukins and cytokeratin-18 concentration reliably decreased by 23.0 % (p˂0.05) (p=0.001). It was found that the comorbid course of the nonalcoholic fatty liver disease is accompanied by an increase in the oxidative stress intensity, which is determined by increased level in the blood of the end products of lipid peroxidation – malondialdehyde – on average 3.8 times (р˂0.05). The use of quercetin in the complex therapy of the nonalcoholic fatty liver disease contributes to a reliable reduction in the oxidative stress intensity, an increase in the antioxidant protection activity (superoxide dismutase), the consequence of which is a significant reduction in the hepatocytes apoptosis process (decrease in cytokeratine-18 level 1.27 times as much).
Keywords: metabolic syndrome; nonalcoholic fatty liver disease; hypolipidemic therapy; quercetin; inflammation